THE EFFECTIVENESS OF USING TOTAL PHYSICAL RESPONSE (TPR) METHODIN TEACHING VOCABULARY IN ELEMENTARY SCHOOL: AN EXPERIMENTAL RESEARCH TO THE 2ND GRADE OF SDN ISOLA 2 BANDUNG - Maya Febiantini Dewi, - (2009)
One of the focus aspects of English learning for young learners is vocabulary. There are several methods in teaching language to develop quantity and quality of student's vocabulary, one of them is Total Physical Response. One of young learners characteristics is experiencing the instruction directly, in other word, learning by doing. TPR is assumed can accommodate this characteristic. This study is going to investigate whether the use of TPR could accommodate this characteristics. Using both quantitative and qualitative research that used experimental study as its framework, this study was aimed at examining the effectiveness of using TPR method in teaching vocabulary in elementary school. The sample of this study was 2nd graders of SDN Isola 2. The data were gained through administering pre-test, posttest and video recording. And the data was analized by using independent t-test and the result of video recording. Data under the study showed that there was a significant result before and after the treatment. It seemed by using TPR, students were more active and motivated to learn English. Therefore, it was proved that TPR was effective to help students improve their vocabulary achievements. So, it is recommended that TPR should be applied as a more innovative English teaching method for young learners.